2022
DOI: 10.1002/adma.202270112
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Bioprinting of Organoids and Optically Tuned Hydrogels to Build Liver‐Like Metabolic Biofactories (Adv. Mater. 15/2022)

Abstract: Volumetric Bioprinting Volumetric bioprinting shapes organoid‐laden constructs into centimeter‐scale assemblies that mimic native liver function. In article number 2110054, Riccardo Levato and co‐workers report the development of a hydrogel‐based bioresin with tunable optical properties to minimize scattering in light‐based printing and ensure high resolution. Organoid viability and maturation is preserved by the shear‐stress‐free printing, and salient liver functions mature in response to the 3D bioprinted ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(54 citation statements)
references
References 0 publications
1
45
0
Order By: Relevance
“…Iod is a nontoxic, water‐soluble, non‐ionic radiocontrast agent that had also been recently used as RI‐matching compound in VP (Figure 1B). [ 30 ] The Iod stock solution (60%) has a significantly higher RI (1.4310) compared to the photoresin and its addition resulted in a linear increase in the photoresins RI up to 1.4195 for Iod 50% (Figure 1B). As described by Kip et al., [ 47 ] the self‐focusing effect due to OMI appears, for a given laser coherence length and intensity, only if the non‐linearity (change in RI due to crosslinking) exceeds a certain threshold.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iod is a nontoxic, water‐soluble, non‐ionic radiocontrast agent that had also been recently used as RI‐matching compound in VP (Figure 1B). [ 30 ] The Iod stock solution (60%) has a significantly higher RI (1.4310) compared to the photoresin and its addition resulted in a linear increase in the photoresins RI up to 1.4195 for Iod 50% (Figure 1B). As described by Kip et al., [ 47 ] the self‐focusing effect due to OMI appears, for a given laser coherence length and intensity, only if the non‐linearity (change in RI due to crosslinking) exceeds a certain threshold.…”
Section: Resultsmentioning
confidence: 99%
“…[ 26,27 ] Recent studies have demonstrated the possibility to create hollow, perfusable structures, using materials from glass to biopolymers and possibly targeting mesoscale vasculature. [ 28–31 ] However, as all the methods described above, also VP falls short in covering resolution range from µm/sub‐µm up to cm, thus currently limiting its application to microfluidic constructs with features >100–200 µm.…”
Section: Introductionmentioning
confidence: 99%
“…They use the recently developed volumetric bioprinting method for the fabrication of organoids, which capture the key functions of the human liver and undergo hepatocytic differentiation with albumin synthesis, liver-specific enzyme activity and have remarkably acquired a native-like cell polarization. 36 transmission. The nerve was then implanted into a synchronous bionic robotic hand system where it showed a real-time high fidelity and high throughput information interaction, both under deformation and cryogenic temperatures.…”
Section: Biomaterials Research In Advanced Materials (Ekaterina Peret...mentioning
confidence: 99%
“…When compared to Matrigel, which has unstable physical properties, biomimetic hydrogels have the advantage of being more controllable and precise as bio-inks. Some biomimetic hydrogels have been applied as bioinks in 3D printing, including liver-like metabolic biofactories, 70 templates for growing soft tissue organoids, 71 fully synthetic vascularisation platform 68 and a crosslinkable microgel composite matrix bath for embedded bioprinting of perfusable tissue constructs and sculpting of solid objects. 72 Overall, these innovative techniques for creating complex tissue structures should be able to maintain a high cell viability and functionality, which could have important implications for tissue engineering.…”
Section: Perspectivementioning
confidence: 99%